The Slipping Magnetic Reconnection and Damped Quasiperiodic Pulsations in a Circular Ribbon Flare - Jing Huang; Baolin Tan; Yin Zhang; Xiaoshuai Zhu; Shangbin Yang; Yuanyong Deng (The Astrophysical Journal, 2024)
The study of circular ribbon (CR) flares is important to understand the three-dimensional magnetic reconnection in the solar atmosphere. We investigate the slipping brightenings and damped quasiperiodic pulsations in a CR flare by multiwavelength observations. During the flaring process, two extreme ultraviolet brightenings (SP1 and SP2) slip synchronously along the ribbon in a counterclockwise direction. The ribbon and fans between them show synchronous enhancement with the microwave and hard X-ray (HXR) CR source. In the magnetohydrostatic extrapolation results and observations, the dome and outer spine display an evident counterclockwise twisting feature. We propose the slipping reconnection occurs between the fan and outer spine in the null point, which covers the region from SP1 to SP2. The fan of SP1 shows the strongest twist and produces the most efficient reconnection. The ribbon after SP1 becomes weak due to the destruction of the fan configuration. The fan of SP2 is in the front of the slipping motion, which initiates new reconnection and brightens the local ribbon. The twisting of the dome continuously promotes new reconnection in the null point, which brightens the ribbon in sequence to display a counterclockwise slipping feature. Thus, the twist of the dome may trigger and dominate the slipping reconnection, and the rotation of the central positive pole could be one possible cause of the twist. After the peak, the microwave and HXR emission shows damped oscillations at a period of 15 s. The collapse of the fan–spine structure may lead to the standing kink oscillations of the fan to modulate the reconnection and particle acceleration process.